Spectra of correlators in the relaxation time approximation of kinetic theory - Matej Bajec; Sašo Grozdanov; Alexander Soloviev (Journal of High Energy Physics)
Abstract The relaxation time approximation (RTA) of the kinetic Boltzmann equation is likely the simplest window into the microscopic properties of collective real-time transport. Within this framework, we analytically compute all retarded two-point Green’s functions of the energy-momentum tensor and a conserved U(1) current in thermal states with classical massless particles (a ‘CFT’) at non-zero density, and in the absence and presence of broken translational symmetry. This is done in 2 + 1 and 3 + 1 dimensions. RTA allows a full explicit analysis of the analytic structure of different correlators (poles versus branch cuts) and the transport properties that they imply (the thermoelectric conductivities, and the hydrodynamic, quasihydrodynamic and gapped mode dispersion relations). Our inherently weakly coupled analysis thereby also enables a direct comparison with previously known strongly coupled results in holographic CFTs dual to the Einstein-Maxwell-axion theories.